Sleep and Respiratory Infections - Boira, Ignacio; Chiner, Eusebi (Seminars in Respiratory and Critical Care Medicine, 2025)
Sleep disorders that involve circadian rhythm disruption and sleep-disordered breathing (SDB) such as obstructive sleep apnea (OSA) are closely linked to respiratory infections. SDB leads to a proinflammatory state due to intermittent hypoxia, sleep fragmentation, increased oxidative stress, and elevation of inflammatory mediators such as tumor necrosis factor (TNF), interleukin-6 (IL-6), and C-reactive protein (CRP). Furthermore, inflammatory mediator levels correlate with SDB severity, especially in people with OSA. Nocturnal microaspiration, gastroesophageal reflux, and associated comorbidities (e.g., obesity) increase the risk of community-acquired pneumonia, viral infections such as SARS-CoV-2, respiratory complications, and death. OSA has been associated with post-COVID syndrome. It also increases the risk of postoperative complications in both adults and children. Circadian rhythm disorders such as insomnia predispose to immune disorders and increase the risk of infection. Chronic conditions such as bronchiectasis, with or without concomitant cystic fibrosis, can lead to structural sleep changes and increase the risk of OSA due to chronic cough, arousals, aspirations, hypoxia, upper airway edema, and overexpression of proinflammatory cytokines. The protective effect of treatment for sleep disorders against respiratory infection is currently unknown. However, in people presenting with respiratory infection, it is important to test for SDB to prevent complications.
Keywords: sleep disordered breathing; circadian rhythm; pneumonia; respiratory infection; obstructive sleep apnea; risk of infection